Broadening the phenotypic spectrum of Beta3GalT6‐associated phenotypes. Issue 10 (23rd June 2021) - Leoni, Chiara; Tedesco, Marta; Radio, Francesca Clementina; Chillemi, Giovanni; Leone, Antonio; Bruselles, Alessandro; Ciolfi, Andrea; Stellacci, Emilia; Pantaleoni, Francesca; Butera, Gianfranco; Rigante, Donato; Onesimo, Roberta; et al.
Abstract: Biallelic mutations in B3GALT6, coding for a galactosyltransferase involved in the synthesis of glycosaminoglycans (GAGs), have been associated with various clinical conditions, causing spondyloepimetaphyseal dysplasia with joint laxity type 1 (SEMDJL1 or SEMDJL Beighton type), Al‐Gazali syndrome (ALGAZ), and a severe progeroid form of Ehlers‐Danlos syndrome (EDSSPD2). In the 2017 Ehlers‐Danlos syndrome (EDS) classification, Beta3GalT6‐related disorders were grouped in the spondylodysplastic EDSs together with spondylodysplastic EDSs due to B4GALT7 and SLC39A13 mutations. Herein, we describe a patient with a previously unreported homozygous pathogenic B3GALT6 variant resulting in a complex phenotype more severe than spondyloepimetaphyseal dysplasia with joint laxity type 1, and having dural ectasia and aortic dilation as additionally associated features, further broadening the phenotypic spectrum of the Beta3GalT6‐related syndromes. We also document the utility of repeating sequencing in patients with uninformative exomes, particularly when performed by using "first generations" enrichment capture methods.